Altitude-induced effects on neuromuscular, metabolic and perceptual responses before, during and after a high-intensity resistance training session - Márquez, G.; Colomer, D.; Benavente, C.; Morenilla, L.; Alic-Fages, C.; Padial, P.; Feriche, B. (European Journal of Applied Physiology, 2023)
Purpose We tested if an acute ascending to 2320 m above sea level (asl) affects corticospinal excitability (CSE) and intracortical inhibition (SICI) measured with transcranial magnetic stimulation (TMS) at rest, before, during and after a traditional hypertrophy-oriented resistance training (RT) session. We also explored whether blood lactate concentration (BLa), ratings of perceived exertion (RPE), perceived muscular pain and total training volume differed when the RT session was performed at hypoxia (H) or normoxia (N).